Guidelines for conducting epidemiological studies of blast injury. Issue 1 (17th April 2018) - Bieler, Dan; Cernak, I; Martineau, L; Bjarnason, S; Franke, A; Kirkman, E; Leggieri, M J; Orru, H; Ouellet, S; Philippens, M; Risling, M G; Sarron, J-C; et al.
Abstract : Blast injuries are often caused by more than one mechanism, do not occur in isolation, and typically elicit a secondary multi-system response. Research efforts often do not separate blast injuries caused by blast waves from those caused by blunt force trauma and other mechanisms. 15 experts from nine different NATO nations developed in the HFM Research Task Group (RTG; HFM-234 (RTG)) 'Environmental Toxicology of Blast Exposures: Injury Metrics, Modelling, Methods and Standards' Guidelines for Conducting Epidemiological Studies of Blast Injury. This paper describes these guidelines, which are intended to provide blast injury researchers and clinicians with a basic set of recommendations for blast injury epidemiological study design and data collection that need to be considered and described when conducting prospective longitudinal studies of blast injury.